Effects of Textural Properties and Surface Oxygen Content of Activated Carbons on the Desorption Activation Energy of Water - Xin Li; Zhong Li; Qibin Xia; Hongxia Xi; Zhenxia Zhao (Adsorption Science & Technology)
This work mainly describes investigations of the effects of pore structure and oxygen content of activated carbons on the desorption activation energy, E d , of water. First, the textural properties and the surface oxygen content as well as the surface acidities of the activated carbons studied were determined by nitrogen adsorption, XPS and Boehm titration methods. The water vapour isotherms of the samples were then measured and temperature programmed desorption (TPD) experiments were conducted to estimate the desorption activation energy, E d , of water on the activated carbons. The effects of pore structure and surface oxygen content of the activated carbons on the magnitude of E d are discussed. The results obtained show that the surface acidities of the activated carbons were in direct proportion to their surface oxygen contents, with the value of E d for water on the activated carbons increasing with increasing surface oxygen content and decreasing pore size of the activated carbons. When the magnitude of the surface acidity was 0.578, 0.436 and 0.338 mmol/g, respectively, the E d for water had corresponding values of 48.61, 41.67 and 37.22 kJ/mol, respectively. The amount of water vapour adsorbed at lower relative humidity increased with increasing surface acidity, whilst it was dependent on the pore volume at higher relative humidity due to pore filling, i.e. the larger the total pore volume of the activated carbons, the larger their adsorption capacities towards for water vapour.